Matemática
lunnacristina13
3

resolva a expressão : a) 5 · (-3) ² + 1 - 1 b) 2⁻² + (1/3)²

+0
(1) Respostas
hellitinho

a) 5 · (-3) ² + 1 - 1 5.  9       +  0   =   45                                    ¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨ b) 2⁻² + (1/3)²  1     +   1²  ----       ----  2²         3² mmc (4,9) = 36 4,9: 2 2,9: 2 1,9: 3 1,3: 3 ------------- 1,1  = 2.2.3.3 = 4.9 = 36  1           1           9 + 4       13 ----   +  ----  =   ---------  = --------  4           9           36         36

Adicionar resposta